Self esteem and values in quality and excellence - Loli Pineda, Alejandro (1998)
The article analyzes the quality human as principal development factor of the organizations. Support that the human quality, in great measure, it is product of the training and development of the self-esteem and that this constitutes the sustenance of the values that they are those which are entrusted with regulating the human conduct. Thus the key of the quality and the success of the man is found substantially in the self-esteem (high) that will lead to establish positive social interactions, between them your performance in the work, creating permanent feedback conditions. Of this manner, the training of the self-esteem and the values are converted into a challenge for the families, for the organization leaders and mainly governmental.